Implementation of the Curriculum 2013 and Merdeka Curriculum Evaluation System in Islamic Religious Education Learning at MTsN 1 Langsa - Rusdi Jauhari; Muhaini Muhaini; Mahyiddin Mahyiddin (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study aims to analyze the implementation of the learning evaluation system for Islamic Religious Education (PAI) at MTsN 1 Langsa by comparing two curriculum approaches, namely Curriculum 2013 (K13) and the Merdeka Curriculum. The main focus of this study is on the planning, implementation, and evaluation instruments applied by PAI teachers within the two curriculum frameworks. This research employs a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation involving PAI teachers, the head of the madrasah, and students. The results indicate that the implementation of learning evaluation in Curriculum 2013 emphasizes structured assessments of knowledge, skills, and attitudes using standardized instruments. In contrast, the Merdeka Curriculum provides greater flexibility for teachers in selecting more contextual evaluation methods that are oriented toward students’ individual competencies. Nevertheless, the implementation of the Merdeka Curriculum presents greater challenges, particularly in terms of teacher readiness and the availability of flexible evaluation tools. This study concludes that each curriculum has its own strengths and limitations in the learning evaluation system, which need to be aligned with the needs and characteristics of learners. These findings are expected to contribute to the development of more effective and adaptive evaluation policies for Islamic Religious Education at the madrasah level